Disasters and Changes in Society and Politics : Contemporary Perspectives from Italy - Antronico, Loredana; Bertin, Mattia; Bosher, Lee; Chmutina, Ksenia; Dall'Ò, Elisabetta; De Pascale, Francesco; Del Pinto, Monia; Fiore, Brunella; Forino, Giuseppe; Forino, Giuseppe; Gugg, Giovanni; Mariani, Enrico; et al. (Bristol University Press, 2024)
From earthquakes to oil spills, Italy is recurrently affected by different kinds of disasters. This book brings a critical perspective to post-disaster reconstruction and recovery, which can impact in both the short- and long- term upon society, politics and organisations. It is often assumed that disaster-hit areas return to normality or even "build back better" thanks to the interventions of experts. Giuseppe Forino considers the complexities of disaster recovery and the sometimes radical changes in individual and collective behaviours that persist following such events. Bringing together the impacts of natural hazards (including climate change and the COVID-19 pandemic), this edited book will stimulate debate on policy and practice in disaster recovery.